Proposta de uma rotina de análise usando o eletrodo de diamante dopado com boro para a determinação simultânea de metais traço em água de coco - Rosa, Thalles Ramon (2015)
The square-wave anodic-stripping voltammetry (SWASV) and boron-doped diamond thin film electrode (BDD) have been proposed for the simultaneous determination of Zn, 11 Cd, Pb and Cu, free and total, in natural and processed coconut water. The optimal values and/or chosen from the experimental design for this technique were: -1500 mV; 240 s; 0.206 mol L-1; 11.56 mV; 55 mV and 100 Hz for the potential; time of deposition; concentration of acetate buffer pH 4.7; step voltage; pulse amplitude and frequency, respectively. The application of SWASV in the processed coconut water I (AI), with no previous digestion provided free Zn and Cu concentrations values of (85,8 ± 5%) and (7.7 ± 9%) µg L-1, respectively. Compared to the ICP OES technique, these concentrations were 33% (230 ± 1%, in µg L-1) of Zn and 154% (5.0 ± 10%, µg L-1) of Cu. In this determination, the concentrations of Cd and Pb were lower than the respective LODICP OES (0.25 and 1.6 µg L-1, respectively). On the other hand, the determination of the total concentration of these analytes was carried out after digestion process assisted by ultrasound. In this method there were used 1.00 mL of natural coconut water of the sample A (NA), 0.8 mL of H2O2 (37% v/v) and 0.6 mL HCl (35% v/v). After the application of the SWASV the concentration values of the digested sample for Zn and Cu were 102% and 46% in response to the values obtained by ICP OES. Again, Cd and Pb were lower than the LOD of both techniques. Alternatively, preliminary studies were conducted by applying SWASV with the same previously cited variables, but using pH 8.0 ammonium acetate buffer to replace the buffer with pH 4.7 to determine the concentration of the four metals in a digested natural sample E (NE). The results obtained for Zn and Cu were respectively 192.6 ± 17 µg L-1 (104% of ICP OES) and 13 ± 3 µg L-1 (), highlighting the great sensitivity obtained for the Cu. At the end of these studies we noted that the use of DDB in conjunction with SWASV is a sensitive and versatile analytical tool which opens new possibilities for the determination of trace metals in natural and digested samples.